Rancang Bangun Perbaikan Faktor Daya Otomatis Berbasis Smart Relay Pada Jaringan Tegangan Rendah Tiga Fasa - Saputra, Ade Chandra; Suwitno, Suwitno; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Power factor is one of the problems in the electric power quality improvement. Power factor value that is too low can result in some electrical equipment can not operate properly. In many ways, low power factor need not cost cheap. To assist in the use of power factor correction capacitor banks to provide reactive power in the system. To improve the power factor is low, then the study will be compensated automatically by using smart relay as a switch to the capacitor bank. Cosphi great start on system is 0,26 lag with the addition of 2,08-33 µF capacitor to cosphi be 0.99 Lag. Keywords: Capacitor Bank, Smart Relay, Power Facto